Let's solve the equation step by step:
2(3m + 2) = 2(m - 4) + 24
First, we need to distribute the 2 to both terms inside the parentheses:
6m + 4 = 2m - 8 + 24
Next, we can combine like terms on both sides of the equation:
6m + 4 = 2m + 16
Now, we can subtract 2m from both sides to isolate the variable:
4m + 4 = 16
Next, we can subtract 4 from both sides of the equation:
4m = 12
Finally, we can divide both sides of the equation by 4 to solve for m:
m = 3
Therefore, the value of m that makes the equation true is 3.
What value of m makes the equation 2(3m + 2) = 2(m - 4) + 24 true?
3
4
5
9
1 answer